DAMPAK PEMILIHAN KEPALA DESA TERHADAP HUBUNGAN KEKELUARGAAN DI DESA LERA KECAMATAN WOTU KABUPATEN LUWU TIMUR PERSPEKTIF SIYASAH SYAR’IYYAH - Fajriani, Fajriani; Teripadang, Andi (Prodi Hukum Tata Negara (Siyasah Syariyyah) Fakultas Syariah dan Hukum UIN Alauddin Makassar, 2022)
The election of the village head often caused prolonged conflicts, resulting in the tenuation of the family cord. This study aims to determine the impact of the village head election on the family system in Lera Village, Wotu District, East Luwu Regency. This research is a qualitative research, with a sociological and syar'i approach. The village head election system that was carried out directly in Lera Village resulted in the tenuous family relationships that had been well established, and even disappointment between supporters sometimes ended in acts of violence. Although some can be resolved in a familial manner, there are also those that must end up in court, and these conditions pose a threat to the continuity of the democratization system at the level of village government. The basic principle of government administration in the concept of siyasah syar'iyyah is the realization of benefits, so that the election of village heads as a process or mechanism for choosing leaders should not cause impacts that can damage the family relationship that has been a characteristic of rural communities.